A Gardos channelopathy associated with nonimmune hydrops and fetal loss. Issue 6 (13th September 2022) - Ghesh, Leïla; Besnard, Thomas; Joubert, Madeleine; Picard, Véronique; Le Vaillant, Claudine; Beneteau, Claire
Abstract: Dehydrated hereditary stomatocytosis (DHS) (MIM#194380) is a rare autosomal dominant disorder of red blood cell permeability, characterized by a partially or fully compensated nonimmune hemolytic anemia. PIEZO1 is the major gene involved with hundreds of families described, some of which present transient perinatal edema of varying severity. A smaller subset of individuals harbors pathogenic variants in KCNN4, sometimes referred as "Gardos channelopathy." Up to now, only six pathogenic variants in KCNN4 have been reported in 13 unrelated families. Unlike PIEZO1 ‐DHS, neither perinatal edema nor fetal loss has ever been observed linked to KCNN4 ‐DHS. We report the first fetal loss due to non‐immune hydrops fetalis related to a pathogenic 28 bp deletion (NM_002250.2: c.1109_1119+17del) in KCNN4 . This observation underlies the need for very close monitoring of pregnancies when one parent is affected by DHS regardless of genotype ( PIEZO1 or KCNN4 ). Abstract : Dehydrated hereditary stomatocytosis (DHS) is a rare autosomal dominant disorder of red blood cell, characterized by a compensated nonimmune hemolysis. PIEZO1 is the major gene involved, with transient perinatal edema observed in few families. Some affected individuals harbor pathogenic variants in KCNN4, sometimes referred as "Gardos channelopathy." Unlike PIEZO1 ‐DHS, neither perinatal edema nor fetal loss has ever been observed in KCNN4 ‐DHS. We report the first fetal loss due to non‐immune hydrops fetalis related to a pathogenic 28 bp deletion in KCNN4 . This observation underlies the need for very close monitoring of pregnancies when one parent is affected by DHS regardless of genotype ( PIEZO1 or KCNN4 ).